Sanātana Vijñāna & Warangal Fort - Bhattacharya, Deepak (Historical Journal, 2023)
Telengana, the new province of India (2014) is explored from a Science Heritage perspective. It is seen she has an ‘impact crater’ of a geological period of the pre-Himalayan (Eocene) period. It has dual rings like complex craters acting as ramparts and hence the entire is the Warangal Fort. This is a case of ‘natural heritage’. Inside it is a Siva temple which is the central piece. It is a case of ‘man-made heritage’ and provides material for the Caption. Temple’s remains (demolished during the Islamic period) are studied from Science and engineering Heritage perspectives. Engrossing field study leads to interesting transpiration that yields a plethora of Hindu Sc & Tech aspects dating to c.13-14th A.D. Astronomically the temple appears to be associated with the star Betelgeuse i.e., Rigel of the Orion constellation (Vana Rājā Kalāpuruṣa Maṇḍala). The 1000-pillar temple complex -Hanamkonda (Han ūmān Hanūmā town) is associated possibly with the same constellation. There are three structures and the layout is alike Orion’s eastern triplet (κ-Ori – ε-Ori -&- α Orionis from S-to-N). These construe archaeo-astronomy (ancient pure science). Historically belongs to the Kakatiya (medieval) extending backward to tribal societies and pre-periods. Preliminary surface scanning of the satellite images of the Hyderabad Muslim heritage region indicates vestiges of a star riangular shaped foundation of a possible erstwhile structure to the west by southwest of the Golconda fort. An excellent example of Vedic Sc. & Tech.